Theoretical Insights into the Excited State Hydrogen Bond and ESIPT Reaction for 2-Amino-3-(2’-Benzoxazolyl)Quinoline and 2-Amino-3-(2’-Benzothiazolyl)-Quinoline (Journal of Atomic and Molecular Sciences, 2018)
Two N-H type excited state intramolecular proton transfer (ESIPT) systems (i.e., 2-amino-3-(2’-benzoxazolyl)quinoline (ABO) and 2-amino-3-(2’-benzothiazolyl)-quinoline (ABT)) have been investigated. Adopting DFT and TDDFT methods coupling with B3LYP functional and TZVP basis set, our simulations about ABO and ABT molecules have successfully reappeared experimental results, based on which the rationality of our calculations is confirmed. Using Atoms in Molecules (AIM) analytical method, we firstly explore the interactions about chemical bond and verify the formation of hydrogen bond N-H•••N for ABO and ABT in the $S_0$ state. Investigating the primary geometrical parameters involved in N-H•••N, we find it should be strengthened in the $S_1$ state. Upon photoexcitation, charge transfer phenomenon is found via frontier molecular orbitals (MOs), and charge redistribution provides the tendency of ESIPT reaction for ABO and ABT. According to our constructed potential energy curves of both $S_0$ and $S_1$ states for ABO and ABT using two kinds of methods (i.e., the elongation of N-H single bond and the weakening of H•••N hydrogen bond), we clarify the ESIPT mechanisms and explain the recovery of four-level reaction cycle. Our searching transition state (TS) structures and simulated intrinsic reaction coordinate (IRC) path further confirm the ESIPT reaction.